2012
DOI: 10.1016/j.jpag.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health Behavior Interventions for U.S. Latino Adolescents: A Systematic Review of the Literature

Abstract: Study Objective To identify sexual health behavior interventions targeting U.S. Latino adolescents. Design A systematic literature review. Setting Peer-reviewed articles published between 1993 and 2011, conducted in any type of setting. Participants Male and female Latino adolescents ages 11–21 years. Interventions Interventions promoting sexual abstinence, pregnancy prevention, sexually transmitted infection (STI) prevention, and/or HIV/AIDS prevention. Main Outcome Measures Changes in knowledge, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…14,40 Our findings point to several cultural variables that may be useful to target in future sexual health interventions. Importantly, these factors should be evaluated in intervention studies to determine whether they can be manipulated, and whether they are causally related to sexual behaviors.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…14,40 Our findings point to several cultural variables that may be useful to target in future sexual health interventions. Importantly, these factors should be evaluated in intervention studies to determine whether they can be manipulated, and whether they are causally related to sexual behaviors.…”
Section: Discussionmentioning
confidence: 73%
“…In a recent literature review of sexual health behavior interventions for Latino youth, Cardoza et al reported that few sexual health programs included components addressing salient cultural values. 14 …”
mentioning
confidence: 99%
“…Few sexual health interventions have been developed and systematically evaluated to reach Hispanic youth [10]. These findings suggest that public health efforts in STD prevention among Hispanic youth may need to be tailored for specific subgroups based on acculturation.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, han participado padres/madres y sus hijos adolescentes, cuando la mayoría de los estudios que se realizan se centran en uno de los dos grupos (Cordova et al, 2014). Por último, se destaca la necesidad de intervenciones sobre salud sexual en adolescentes latinos desde una perspectiva socio-ecológica, en la que se tengan en consideración múltiples niveles de influencia (individual, familiar, comunitario, entre otros) (Cardoza, Documét, Fryer, Gold, & Butler, 2012;.…”
Section: Discussionunclassified